Rapidly progressive adult-onset neuronal intranuclear inclusion disease beginning with autonomic symptoms: a case report - Zhu, Yi; Yang, Qian; Tian, Yun; Fan, Weibing; Mao, Xinfa (Frontiers in Neurology, 2023)
Background Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease that can affect the nervous and other systems of the body. Its clinical manifestations are complex and easily misdiagnosed. Adult-onset NIID beginning with autonomic symptoms such as recurrent hypotension, profuse sweating, and syncope has not been reported. Case presentation An 81-year-old male was admitted to the hospital in June 2018 due to repeated episodes of hypotension, profuse sweating, pale complexion, and syncope for 3 years, and progressive dementia for 2 years. DWI was not possible due to the presence of metal residues in the body. Cutaneous histopathology revealed sweat gland cell nuclear inclusions and immunohistochemistry showed p62 nuclear immunoreactivity. Blood RP-PCR identified an abnormal GGC repeat expansion in the 5′UTR of the NOTCH2NLC gene. Accordingly, this case was diagnosed as adult-onset NIID in August 2018. The patient subsequently received vitamin C nutritional support, rehydration, and other vital signs maintenance treatments during hospitalization, but the above symptoms still recurred after discharge. With the development of the disease, lower extremity weakness, slow movement, dementia, repeated constipation, and vomiting appeared successively. In April 2019, he was hospitalized again for severe pneumonia, and died of multiple organ failure in June 2019. Conclusion The presented case exemplifies great clinical heterogeneity of NIID. Some patients may have neurological symptoms and other systemic symptoms simultaneously. This patient started with autonomic symptoms, including recurrent episodes of hypotension, profuse sweating, pallor, and syncope, which progressed rapidly. This case report provides new information for the diagnosis of NIID.